Perancangan Sistem Informasi Akuntansi Pembayaran Angsuran Kredit Usaha Kecil Menengah Kebawah (UKM) ( Studi Kasus Pada Koperasi Syari’ah Simpan Pinjam Baitut Tamwil Muhammadiyah Bina Insani Cabang Sukajadi Kota Bandung ) - Titan Parama Yoga (LPPM UNIBI, 2021)
Koperasi as a forum for business activities that are close to the community are also required to keep up with developments in technology and business. This is related to improving services to its members. This demand is not without reason because it is also seen from the perspective of competition. The increase in services provided by koperasi can also be used by koperasi to develop their business fields so that they can better support the economy of members in particular and society in general. The Accounting Information System for small and medium business (UKM) loan installment payments which will be designed at the KSPS BTM Bina Insani has the aim not only of improving services but also transparency of management, distribution and even reporting of savings and loans which have been one of the business sectors of the BTM KSPS. Bina Insani. The method of designing an accounting information system for small and medium business (SME) loan installments uses the waterfall method which in each stage will be evaluated whether it is in accordance with the needs and desires of the KSPS BTM Bina Insani where the process will start from planning and analyzing needs for anything which will be designed in the accounting information system for small and medium business (UKM) credit installment payments, the design of each menu is continued with coding and ends with testing of the system whether it is running well and as needed so that the accounting information system for credit installment payments small and medium enterprises (UKM) which will be designed later can help the KSPS BTM Bina Insani to maximize the payment of credit installments for small and medium enterprises (UKM) with trust.